Evaluation in silico of eucalipitol monoterpene toxicity (Research, Society and Development, 2020)
Recent studies related to natural products have shown greater interest in analyzing their toxicological profile, since there are requirements for regulation of safe levels that promote better efficiency of the pharmacological potential of these medicines of natural origin. The present study seeks to analyze through in silico tests the toxicity of eucalyptol monoterpene. For this, the admetSAR® tool was used, a free online database, available at http://lmmd.ecust.edu.cn/admetsar1/, and with this system it was possible to observe toxicity data such as: toxicity AMES, carcinogenicity profile, carcinogenesis and acute oral toxicity. From the in silico analysis, eucalyptol did not show AMES toxicity or degree of carcinogenicity, the carcinogenic profile was considered low and its acute oral toxicity classified as grade III, considered moderate. The research points to a low toxicity of the eucalyptol monoterpene, its silica analysis data suggest that the substance is a good candidate for the development of therapeutic alternatives, however, for a better understanding of the substance's toxicological profile, in vitro and in vitro studies should be performed. alive.